Introduction of an interdisciplinary heart team‐based transcatheter aortic valve implantation programme: short and mid‐term outcomes. Issue 9 (September 2014) - Martínez, G. J.; Seco, M.; Jaijee, S. K.; Adams, M. R.; Cartwright, B. L.; Forrest, P.; Celermajer, D. S.; Vallely, M. P.; Wilson, M. K.; Ng, M. K. C.
Abstract Background Transcatheter aortic valve implantation (TAVI) has been developed to treat symptomatic aortic stenosis in patients deemed too high risk for open‐heart surgery. To address this complex population, an interdisciplinary heart team approach was proposed. Aim Present the short‐ and mid‐term outcomes of the first 100 patients in the Royal Prince Alfred Hospital multidisciplinary TAVI programme. Methods Single‐centre registry. Baseline and procedural data were prospectively recorded. Outcomes were recorded according to Valve Academic Research Consortium – version 2 guidelines. Results All patients underwent a comprehensive interdisciplinary pre‐procedural evaluation. Sixty‐eight transfemoral and 32 transapical implantations were performed. Mean age was 82 (±8.9) years old with an average logistic EuroSCORE of 33. Although 13 procedures had major complications, there was no intraprocedural mortality. During the first month, 9% of patients were re‐admitted due to heart failure and 13% had a permanent pacemaker implanted. A 3% 30‐day and 8% follow‐up (mean 17 months) mortalities were recorded. While no significant differences in the rate of complications were found between the first and second half of the experience, all cases of mortality within 30 days (n = 3) occurred in the initial half. Sustained haemodynamic results were obtained with TAVI (immediate mean aortic valve gradient reduction from 47 to 9 mmHg; 1‐year echocardiographic gradient 9.9 mmHg, with no moderate or severe aortic regurgitation). Conclusion Excellent results can be achieved with TAVI in very high‐risk patients at an Australian institution. A comprehensive evaluation based on a heart team can overcome most of the difficulties imposed by this challenging population.